Estimated pulse wave velocity as a measure of vascular aging. - Kevin S Heffernan; Lee Stoner; Andrew S London; Jacqueline A Augustine; Wesley K Lefferts (PLoS ONE, 2023)
Background Carotid-femoral pulse wave velocity (cfPWV), the referent measure of aortic stiffness, is an established measure of vascular aging. In studies where cfPWV cannot be measured, alternative methods are needed to help promote research on vascular aging. This study examines the construct validity of a measure of PWV estimated from age and blood pressure (ePWV). The specific aims of the study are to: 1) explore the strength of association between ePWV, cfPWV, and other established measures of vascular aging; 2) examine the sensitivity and specificity of elevated ePWV (≥10m/s) in relation to elevated cfPWV (≥10m/s). Methods We measured cfPWV in two-hundred and fifty-two adults (mean age 57±12 years, 48% female) and calculated each participant's ePWV from their age and brachial blood pressure. Additional measures of vascular aging included: carotid intima-media thickness (cIMT); carotid stiffness measured as elastic modulus (cEp); and carotid augmentation index (cAIx). Results The correlations between cfPWV and measures of vascular aging were: cEp (r = 0.36), cIMT (r = 0.49), and cAIx (r = 0.04). The correlations between ePWV and measures of vascular aging were: cEp (r = 0.45), cIMT (r = 0.60), and cAIx (r = 0.24). The correlation between ePWV and cfPWV was (r = 0.67). The sensitivity and specificity of elevated ePWV (≥ 10 m/s) for concomitantly identifying high cfPWV (≥ 10 m/s) were 85.4% and 73.0% respectively. Conclusion ePWV is associated with established measures of vascular aging, such as carotid thickness, carotid stiffness and carotid augmentation index. ePWV may be a useful tool to help promote research on vascular aging.